2022
DOI: 10.3233/ves-190749
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of persistent postural perceptual dizziness patients in a multidisciplinary dizziness clinic

Abstract: BACKGROUND: Persistent Postural Perceptual Dizziness (PPPD) is a newly defined condition which was added to the International Classification of Vestibular Disorders in 2017. Little is known about its impact on patients. OBJECTIVE: The goal of this study was to analyze the symptomology, epidemiology and impact of PPPD on patients. METHODS: A retrospective chart review was done to identify patients who attended the Multidisciplinary Dizziness Clinic (MDC) and were diagnosed with PPPD. Responses to demographic qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Since its international classification by the Bárány Society [ 37 ], PPPD is increasingly recognised as the single most common vestibular syndrome in specialised outpatient clinics [ 38 ] and likely represents the vast majority of patients referred to vestibular rehabilitation [ 36 ]. People living with PPPD have poor quality of life, severe dizziness handicap and an elevated risk of anxiety and depression [ 3 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since its international classification by the Bárány Society [ 37 ], PPPD is increasingly recognised as the single most common vestibular syndrome in specialised outpatient clinics [ 38 ] and likely represents the vast majority of patients referred to vestibular rehabilitation [ 36 ]. People living with PPPD have poor quality of life, severe dizziness handicap and an elevated risk of anxiety and depression [ 3 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients with PPPD were female in the present study (female/male ratio: 2.58/1). Previous studies have also reported female preponderance ( 16 18 ). When divided into four groups based on VEMP and vHIT findings, isolated otolith dysfunction was the most common, accounting for 44.2% of patients with PPPD.…”
Section: Discussionmentioning
confidence: 79%
“…Psychosocial factors are also associated with dizziness and chronic dizziness. Previous studies have reported that chronic dizziness is partially related to ‘psychogenic’ causes, and may also cause secondary anxiety or depression [ 14 , 15 ]. Mental disorders, including anxiety disorders, frequently co-occur with balance problems [ 8 , 16 ].…”
Section: Introductionmentioning
confidence: 99%